Levels of C-Reactive Protein In Pregnant Women With Periodontitis And Gingivitis - admin, admin (2018)
Objective. To determine whether periodontal disease, specifically chronic periodontitis and gingivitis severe, mild and mild; stimulate increased levels of PC-R. Determine which of periodontal disease leads to greater increase in PC-R. Materials and method. Correlational study, observational and retrospective. The sample consisted of 136 pregnant women divided into 3 groups: 1) Pregnant women with chronic periodontitis, 2) Pregnant women with severe or moderate gingivitis, 3) Pregnant women with mild gingivitis. Every pregnant woman I request a blood test to detect plasma levels of PC-R. Each pregnant woman was registered in a form collection of data, which indicated the level of PC-R in mg/l, IHO-S, IG and finally the periodontograma. Results. The average level of PC-R in the CP group is 4.53mg/l in the GSM group is 1,53 mg/l in the group GL is 3,77 mg/l, with the mean difference between CP and GSM group, statistically significant (p=0,002), while the mean difference between the CP and GL group is not statistically significant (p=0,371). Conclusions. Periodontal disease stimulates increased levels of PC-R. Chronic periodontitis stimulates a greater increase in the level of PC-R compared to gingivitis severe, moderate and mild.